THE DEPENDENCE OF MAGNETIC SUSCEPTIBILITY ON SOIL’S HUMIDITY - SUKHORADA, A.; KRUHLOV, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The study of soil’s magnetic susceptibility during the desiccation. The application of main kinds magnetic susceptibility in soil’s studies is made comparison.